Implementasi Algoritme SPECK dalam Sistem Monitoring Sumber Daya pada Raspberry Pi - Yohanes Heryka Febriarso; Ari Kusyanti; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Monitoring system is common this time. However, security system needs attention. Because if unauthorized people controls the data from monitoring system, it can endanger owner of monitoring system. Aspect that need to guarded in monitoring system is confidentiality. SPECK algorithm can fulfill confidentiality security and has advantage of low specifications system. SPECK algorithm is implemented in monitoring system on manager and agent when sending and receiving data. Tests includes test vectors, performance, sniffing attacks and known plaintext attacks. Time for monitoring system process encryption has an average 1,780.738 ms on Raspberry Pi 0 W, 799.173 ms on Raspberry Pi 2 and 481.7921 ms on Raspberry Pi 3. Time to process decryption has an average 2,007.717 ms on Raspberry Pi 0 W, 880.4057 ms on Raspberry Pi 2 and 508.9488 ms on Raspberry Pi 3. Data amount before and after encryption is 524 byte in resource, network and disk scenarios. Results of test vector test is same as the SPECK paper so they declared successful. Sniffing test also successful because when checked using Wireshark application, contents of the packet is ciphertext. In known plaintext attack test, the test was successful because the resulting ciphertext failed to decrypt by brute force.